COVID-19: Uncertainties from Conception to Birth - Carvalho, Bruno Ramalho de; Adami, Karina de Sá; Gonçalves-Ferri, Walusa Assad; Samama, Marise; Ferriani, Rui Alberto; Marcolin, Alessandra Cristina (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Scientific information on the impact of the new coronavirus (SARS-CoV-2) on the health of pregnant women, fetuses and newborns is considered of limited confidence, lacking good-quality evidence, and drawing biased conclusions. As a matter of fact, the initial impressions that the evolution of COVID-19 was no different between pregnant and non-pregnant women, and that SARS-CoV-2 was not vertically transmitted, are confronted by the documentation of worsening of the disease during pregnancy, poor obstetric outcomes, and the possibility of vertical transmission. The present article aims to compile the data available on the association of COVID-19 and reproductive events, from conception to birth.
Keywords: COVID-19; severe acute respiratory syndrome coronavirus 2; ovary; testis; conception; pregnancy